Snail Shell-Clay Ceramic Composites as Sustainable Raw Materials for High-Voltage Insulators - TOBINS, Ferguson H.; ARUDI, Ishiaka S.; NURUDEEN, Abdulhakeem H. (FUDMA Journal of Engineering and Technology, 2026)
This study investigates the potential of Giant African Land Snail (GALS) shell–clay ceramic composites as raw materials for high-voltage insulators. The primary aim was to evaluate the influence of firing temperature on the physical properties of these composites and determine their suitability for electrical applications. Crushed GALS shell particles (63 μm and 75 μm) were blended with clay (<120 μm) in varying ratios to produce composites designated 631090, 632080, 751090, and 752080, alongside a pure clay control (C100). Samples were fired at 1160°C, 1180°C, and 1200°C. Physical properties, including shrinkage, water absorption, porosity, and bulk density, were assessed following ASTM standards (1985a). Dry shrinkage remained within acceptable limits (3.6%), while fired shrinkage increased with temperature. Notably, sample 752080 exhibited reduced shrinkage (4.89% at 1200°C) compared to the control (5.93%), indicating that snail shell inclusions constrained contraction. Water absorption and porosity decreased with increasing firing temperature, while density improved, particularly in shell-containing composites. Above 1180°C, partial fusion and glassy phase formation enhanced densification and mechanical strength. Firing at 1200°C produced optimal results, yielding composites with reduced porosity, improved density, and controlled shrinkage. These findings demonstrate that GALS shell–clay ceramics are promising candidates for the manufacture of durable high-voltage insulators, effectively bridging biomimetic inspiration with industrial application.